ANALISIS PERFORMA KRIPTOGRAFI RSA PADA WINDOWS 11 DENGAN PYTHON DAN APLIKASI NZXT CAM - Gunawan, Yusuf Atha; Yuda, Marutha Wira; Bintari, Salsabila Wahyu; Kardian, Aqwam Rosadi (Telkom University, 2023)
This research aims to analyze the performance of RSA cryptography on the Windows 11 operating system, implemented using Python and the NZXT CAM application. A quantitative approach was employed, utilizing a processor with specifications of 2.80GHz, 8 cores, and 16 GB RAM. Data were collected through the NZXT CAM benchmark application, measuring CPU and memory usage during RSA key generation, encryption, and decryption processes. The findings reveal a direct correlation between the length of the RSA key and both CPU load and the time required for cryptographic processes. It was found that longer RSA keys result in increased computational resource usage. For instance, a 1024-bit RSA key averages 10% CPU load and 53.1 MB memory, while a 2048-bit key increases to 11.6% CPU load and 53.4 MB memory. A 4096-bit key requires 10.6% CPU load with similar memory usage, but the processing time increases from 2.5 seconds to 27.7 seconds. The conclusion of this study provides significant insights for the development of security applications on Windows 11, particularly in balancing key length and resource usage. Further research is recommended to evaluate RSA performance on various hardware configurations. Key Words: RSA Cryptography, Windows 11, Python, NZXT CAM, Resource Utilization